STRATEGI PENGEMBANGAN BISNIS UMKM ORANG ASLI PAPUA DI KABUPATEN MANOKWARI - Mayor, Oktofina; Allo, Albertus Girik; Yap, Rumas Alma (Lensa Ekonomi, 2025)
This study aims to analyze the business development strategy of Micro, Small, and Medium Enterprises (MSMEs) managed by Indigenous Papuans in Manokwari Regency. Using qualitative case study approach. Data were collected from 18 MSMEs actors through interviews, observation, and documentation. The SWOt analysis revealed that the main strenghts of OAP MSMEs are excellent service, while weaknesses include limited capital and lack of product variety. Opportunities come from government support and favorable trends toward local products, while threads include business competition and market access. An aggressive (S-O) strategy is recommended. The findings are expected to serve as a reference for sustainable MSME emprowermwnt policies.